Diagnosis and management of subdural hematoma: a review of recent literature - Alshora, Wed; Alfageeh, Mohammed; Alshahrani, Salman; Alqahtani, Saeed; Dajam, Abdulrahman; Matar, Mutaz; Ashour, Rakan; Alasmari, Atif; Alqhtani, Abdulrhman (International Journal Of Community Medicine And Public Health, 2018)
Subdural hematoma is extra-cerebral accumulation of blood between the dura matter and the subarachnoid layer. Subdural hematoma can be associated with significant long-term morbidities and high rates of mortality. The mortality following subdural hematoma can be as high as 32%, and recurrence rates can reach 33%. Acute subdural hematoma is an emergency and requires prompt diagnosis using CT most of the time, and management requires surgery as well as reversal of anticoagulants. We conducted this review using a comprehensive search of MEDLINE, PubMed, and EMBASE, January 1985, through February 2017. The following search terms were used: emergency management of subdural hematoma, subdural hematoma, CT vs. MRI in diagnosis of subdural hematoma, treatment of subdural hematoma. In this review, our aim is to study the etiology of subdural hematoma and understand how it should be diagnosed and managed. Subdural hematoma are clinical emergencies that require immediate and rapid management to prevent significant morbidity and mortality. They can be grouped into acute, subacute, or chronic, with the acute type being the most dangerous and associated with the highest mortality rates. Subdural hematoma is diagnosed using CT or MRI imaging. Management of a patient with subdural hematoma includes resuscitation followed by control of the bleeding. Controlling intracranial pressure is an important factor for predicting the outcomes of subdural hematoma, and should thus be continuously monitored and corrected.